7x+3=-3x-5

Simple and best practice solution for 7x+3=-3x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3=-3x-5 equation:


Simplifying
7x + 3 = -3x + -5

Reorder the terms:
3 + 7x = -3x + -5

Reorder the terms:
3 + 7x = -5 + -3x

Solving
3 + 7x = -5 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 7x + 3x = -5 + -3x + 3x

Combine like terms: 7x + 3x = 10x
3 + 10x = -5 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 10x = -5 + 0
3 + 10x = -5

Add '-3' to each side of the equation.
3 + -3 + 10x = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 10x = -5 + -3
10x = -5 + -3

Combine like terms: -5 + -3 = -8
10x = -8

Divide each side by '10'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 13+n/(-7)=0 | | 13+n/(-7)= | | -3p+8=6-(7p+5) | | 25x+4=5 | | v^2-9v=0 | | (5x+5)= | | -2x(4+3x)=6-4x | | 0.12-0.03(x+3)=0.04(1-x) | | 8+-3x=7x+8 | | 6(x+5)+4=48 | | -7v+2=-9(v+2) | | 2x+23=-3(2x-1) | | 15-[3+7y-4(y+4)]=-4(3y-6)-[9(y-1)-15y+14] | | 3x-14x+25=2-6x-12 | | 36x-1=-8 | | 9+6x-8=6x+33-4x | | 3(m-8)=4(m+4) | | 25x^2+4=5 | | 4(8-x)-7-x=22 | | 4x-3=-0 | | 2(6ax+y)=11ax-7y | | 0.2(6)+x=0.4(6+x) | | 11-9A-2A=5E-3A-2 | | 4u^2-8u+3=0 | | -3y+7.4=20.9 | | 5X+9=11-5 | | .4x+.2(6)=x+6 | | 6x-(2x-4)=40 | | 4a-(5-a)=3(a+2) | | 6x^2+21x-15=0 | | 9x^2-81=12 | | 0.43=in(y) |

Equations solver categories